2021
DOI: 10.1007/s12206-021-0604-2
|View full text |Cite
|
Sign up to set email alerts
|

Design of flat broadband sound insulation metamaterials by combining Helmholtz resonator and fractal structure

Abstract: A new sound insulation metamaterial (SIM) is designed by combining a Helmholtz resonator and a fractal structure for sound insulation in the frequency range of 600 to 1700 Hz. Using a fractal-based internal structure, the designed hybrid SIM shows a relatively constant value of sound transmission loss (STL) over the target frequency range. The basic concept of this work is to develop two functional parts working in each effective frequency range. One is a Helmholtz resonance structure that operates with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This quality can also make them spaceefficient, making them particularly suitable for application in buildings. This category can also include designs where the HR necks have a shared opening or waveguide [8]. If the waveguide is only opened to a source room, the resulting HR array can be considered an absorptive panel.…”
Section: Hr Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…This quality can also make them spaceefficient, making them particularly suitable for application in buildings. This category can also include designs where the HR necks have a shared opening or waveguide [8]. If the waveguide is only opened to a source room, the resulting HR array can be considered an absorptive panel.…”
Section: Hr Arraysmentioning
confidence: 99%
“…The use of acoustic metamaterials is a promising approach to address the low-frequency noise problem more effectively. Research has demonstrated that resonant absorbers, which incorporate arrays of Helmholtz resonators (HRs) with varying resonant frequencies, can provide effective sound absorption in increasingly broader fre-quency spectra [5][6][7][8]. Additionally, HR arrays can be designed to serve as sound barriers capable of achieving good transmission losses while maintaining open cavities for airflow [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic metamaterials [2][3][4][5][6] and acoustic metasurfaces [7][8][9][10] are typical subwavelength structures. Common structure types are Helmholtz resonators, [11][12][13] membrane resonators, 14,15) Fabry-Pérot (FP) cavities, [16][17][18][19][20][21][22] and fractal structures. 23,24) Seoung-HoBaek et al 12) combined a Helmholtz resonator with a fractal structure 23) and designed a sound-insulation metamaterial to reach an average sound-transmission loss of 16.34 dB in the frequency range of 600-1700 Hz.…”
mentioning
confidence: 99%
“…Common structure types are Helmholtz resonators, [11][12][13] membrane resonators, 14,15) Fabry-Pérot (FP) cavities, [16][17][18][19][20][21][22] and fractal structures. 23,24) Seoung-HoBaek et al 12) combined a Helmholtz resonator with a fractal structure 23) and designed a sound-insulation metamaterial to reach an average sound-transmission loss of 16.34 dB in the frequency range of 600-1700 Hz. Similarly, Wu et al 16) designed the coupling structure of microperforated and Fabry-Pérot (FP) folding channels and effectively absorbed sound waves below 500 Hz.…”
mentioning
confidence: 99%